KEABSAHAN PENGISIAN PENJABAT KEPALA DAERAH DARI TENTARA NASIONAL INDONESIA - Fahri Bachmid (Legal Standing : Jurnal Ilmu Hukum, 2023)
Holding simultaneous local elections in 2024 will result in vacancies in the positions of regional heads in some regions. To overcome this impact, the government appointed and authorized active TNI to become PJ Regents, even though the provisions stated that filling the position of the regional head was the position of Pratama high leadership, who came from the State Civil Apparatus group. In this study, the authors utilized normative juridical research methods with a statutory approach, also called the approach, the approach, and a conceptual approach, also called the conceptual approach. That the appointment and appointment of the TNI to be active in filling the position of regional head violates the laws and is contrary to the principles of good governance. The active presence of the TNI in civilian jobs has damaged civilian supremacy, which has been fought for during the reform period to abolish the Dwifungsi ABRI doctrine.